Controlling false discovery rates in factorial experiments with between-subjects and within-subjects tests - Schoen, Eric D; Rubingh, Carina M; Wopereis, Suzan; van Erk, Marjan (BMC research notes, 2013)
The False Discovery Rate (FDR) controls the expected number of false positives among the positive test results. It is not straightforward how to conduct a FDR controlling procedure in experiments with a factorial structure, while at the same time there are between-subjects and within-subjects factors. This is because there are P-values for different tests in one and the same response along with P-values for the same test and different responses. We propose a procedure resulting in a single P-value per response, calculated over the tests of all the factorial effects. FDR control can then be based on the set of single P-values. The proposed procedure is very easy to apply and is recommended for all designs with factors applied at different levels of the randomization, such as cross-over designs with added between-subjects factors. NCT00959790.